Runyon v. McCrary Should Not Be Overruled - Marvin E. Frankel (Washington University Law Quarterly, 1989)
I shall be arguing that in all the pertinent circumstances, Runyon v. McCrary should not be overruled unless it was grossly, utterly, and destructively wrong. Obviously, I believe no such demonstration is possible.